2021
DOI: 10.1038/s41598-021-87356-y
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a low-latitude ionospheric trough associated with the inner radiation belt

Abstract: The dynamics of ionospheric troughs that developed during a great geomagnetic storm on 11–13 April 2001 are studied using measurements of electron density obtained by the CHAMP satellite at an altitude of 410–465 km. Subauroral, mid-latitude and low-latitude troughs were observed at nighttime, sometimes simultaneously. The subauroral trough is usually defined as the main ionospheric trough, whereas the mid-latitude trough is associated with the magnetospheric ring current. It appeared at the beginning of the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
3
3
0
Order By: Relevance
“…Statistical analysis also confirmed that the RIT is more often formed at the longitudes of America, as suggested in a recent study (Karpachev, 2021b). This is because the precipitation of energetic particles occurs most intensively at longitudes with a weak geomagnetic field.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Statistical analysis also confirmed that the RIT is more often formed at the longitudes of America, as suggested in a recent study (Karpachev, 2021b). This is because the precipitation of energetic particles occurs most intensively at longitudes with a weak geomagnetic field.…”
Section: Discussionsupporting
confidence: 85%
“…This is a typical situation for almost any storm. We also noted another low‐latitude trough during pass 25 on December 28, 2002, which was discovered and described earlier in (Karpachev, 2021b).…”
Section: Longitudinal Variations In Rit Position and Occurrence Proba...supporting
confidence: 84%
See 2 more Smart Citations
“…During the recovery phase on the night of 13 October (DOY = 286), a larger depletion region emerges at lower latitudes that is around 15° wide in latitude with an equatorward edge at ∼30°N that is quite sharp. It is possible that this is a combination of multiple lower latitude troughs (e.g., A. T. Karpachev (2021)) whose boundaries have merged/blurred. However, this is purely conjecture given the lack of definitive features along the latitude direction within the TEC data.…”
Section: Data and Analysismentioning
confidence: 99%